Comparative analysis of the use of lipid modifying agents in the Republic of Serbia and Nordic countries in the period 2015-2017 - Martić Nikola B.; Zečević Dragan D.; Đurđević Milena V.; Milijašević Dragana S.; Tomić Nataša Z.; Lalić-Popović Mladena N.; Todorović Nemanja B.; Medin Danilo V.; Mićanović Branimir B.; Milijašević Boris Ž. (Srpsko lekarsko drustvo, 2020)
Introduction: Cardiovascular diseases are the leading cause of death both in Serbia and in the rest of the world. It has been shown that as many as 80% of them are preventable. Control of serum lipid levels is one of the most important tasks of cardiovascular diseases prevention. Aim: The aim of the study was to analyze the use of serum lipid-modifying drugs in Serbia, Norway and Finland in the period 2015-2017. Methods: Data on drugs use during 2015, 2016 and 2017 were taken from the official websites of national drug regulatory authorities: the Serbian Medicines and Medical Devices Agency, the Norwegian Institute of Public Health and the Finnish Medicines Agency. Use was expressed as DDD/1000 inhabitants/day according to the Anatomical Therapeutic Chemical classification. Results: The share of drugs used for treatment of cardiovascular diseases in total drugs use was the largest in all three countries during the observed period. The use of lipidmodifying agents was 3-4 times lower in Serbia than in Norway or Finland. Of all lipidmodifying drugs, statins are most commonly prescribed in all three countries. Atorvastatin and rosuvastatin are the most widely used in Serbia, and simvastatin and atorvastatin in Norway and Finland. Conclusions: Use of lipid-modifying drugs in Serbia is lower than in Norway and Finland, but it is constantly increasing. This use in Serbia still represents the smallest share of all drugs for the treatment of cardiovascular diseases.